Plastics - Cassou, Emilie (World Bank, Washington, DC, 2018)
Although the agricultural sector is not the largest user of plastics, their rapid appearance on farms the world over is quietly turning into a substantial pollution concern. Versatile and economical as they are, plastics are found all over farms. From machines to mulches, they are the stuff of bags and tubs, of tubes and tools, of tags and trays, and of pots and twine. Plastic films are used to cover greenhouses and hug plants around the root zone. Other kinds of plastics are used as ingredients in chemicals. Farms use millions of tons of plastics each year, costing them billions of dollars, a testament to how useful they are. To the extent that they can help to save water, dissuade pests, suppress weeds with less reliance on chemicals or fire, and save fuelby lightening equipment and containers, some of their wide-ranging benefits include ecological ones. Yet more than unsightly, discarded plastics can damage farmland and cause harm to humans and wildlife alike, making their celebrated durability a long-term pollution and public health worry.